Assessment of medication knowledge and adherence among patients under oral chronic medication treatment in community pharmacy settings - OKUYAN, BETÜL; SANCAR, MESUT (WILEY PERIODICALS, INC, 2013)
Purpose This study aimed to determine whether there is a relationship between the lack of medication knowledge and the self-reported rates of patient medication adherence. Methods Patients eligible to participate in the study had been taking oral medication at least once daily over the course of a minimum of three consecutive months before recruitment to the study. All participants were older than 18 years. The level of each patient's knowledge of his or her medication was randomly assessed by a trained fifth-year pharmacy student through an adapted questionnaire. In addition, patient adherence was evaluated via utilization of the Morisky Medication Adherence Scale. Results Of the 765 study participants (mean +/- SD age = 55.45 +/- 15.05 years, range = 2091 years, 56.2% women), 58.0% reported adherence to their medication regimen and 64.5% professed optimal knowledge of their medication. The mean duration of medication utilization was 26.77 +/- 40.62 months (range = 3504 years). A statistically significant correlation exists between the total medication knowledge score on the questionnaire and the level of medication adherence (r=0.964, p<0.001). Conclusion Improvement in the patient's knowledge of medications taken would bear a positive effect on medication adherence. Copyright (c) 2012 John Wiley & Sons, Ltd.
Keywords: community pharmacy; medication adherence; medication knowledge; pharmacoepidemiology; PRESCRIBED MEDICINES; ASSOCIATION; MANAGEMENT; PREDICTORS; LITERACY; BELIEFS; OLDER